Español - Ocsa Campana, Lizbeth Alexandra (2025)
In the present research work, the following hypothesis will be analyzed: the effect of tourism is relevant in economic growth. Starting from a literary review, there are cases where this hypothesis is relevant, such as the case of Turkey where more tourism implied an increase in GDP but in turn pollutes the environment, this article belongs to one of ten articles with which which was worked under the same hypothesis. The formulation for this work is to carry out the Johansen cointegration tests, from there to elaborate an error correction model (VEC) to analyze the Granger causality, once the methodology has been applied, the results show that the sector has a significant impact. to economic growth.